2021
DOI: 10.1177/26323524211019056
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning among older Canadians amid the COVID-19 pandemic: a focus on sexual orientation

Abstract: Objectives: The COVID-19 pandemic has led to death and hardship around the world, and increased popular discourse about end-of-life circumstances and conditions. The extent to which this discourse and related pandemic experiences have precipitated advance care planning (ACP) activities was the focus of this study with a particular emphasis on sexual orientation. Methods: A large, national online survey was conducted between 10 August and 10 October 2020 in Canada. The final sample of 3923 persons aged 55 and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These results have implications beyond how LGBT persons, and especially GB men, adhere to public health mandates and approach the COVID-19 pandemic. de Vries et al [31], for example, make inferences to these same phenomena in their analyses of Advance Care Planning (ACP) among older LGBT persons, drawing from the same sample as the present study. They found that since the onset of the COVID-19 pandemic, LGBT persons were 1.6 times more likely than were cisgender heterosexual persons of comparable age to have begun or completed at least one of the following: a will, durable power of attorney, Advance Directives, and/or a Representation Agreement.…”
Section: Implications For End-of-life Carementioning
confidence: 88%
“…These results have implications beyond how LGBT persons, and especially GB men, adhere to public health mandates and approach the COVID-19 pandemic. de Vries et al [31], for example, make inferences to these same phenomena in their analyses of Advance Care Planning (ACP) among older LGBT persons, drawing from the same sample as the present study. They found that since the onset of the COVID-19 pandemic, LGBT persons were 1.6 times more likely than were cisgender heterosexual persons of comparable age to have begun or completed at least one of the following: a will, durable power of attorney, Advance Directives, and/or a Representation Agreement.…”
Section: Implications For End-of-life Carementioning
confidence: 88%
“…Some studies noted a need for adequate ACP training for clinicians as a barrier [ 76 , 91 , 142 ]. Moreover, the findings of our review indicate that certain communities experienced or were vulnerable to a lack of engagement in ACP due to a combination of factors; disparities in health education [ 90 ], cultural and religious beliefs [ 57 , 86 , 90 , 142 ], socioeconomic challenges [ 57 , 140 ], a general distrust in the healthcare system [ 65 , 124 , 125 , 137 ], and racial or ethnic barriers [ 53 , 90 , 124 , 140 ] played significant roles. These factors were compounded by the pandemic’s exacerbation of healthcare access disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the education and resources offered to healthcare professionals, public-facing ACP education and resources for patients and family members were also identified as facilitators for ACP [ 64 , 65 , 66 , 69 , 72 , 80 ]. The increased availability of resources and education for patients and families has been vital in facilitating ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows mixed results regarding the likelihood of successful completion of ACP between LGBTQIA individuals and their heterosexual counterparts. Some studies show an increased rate of ACP completion 14,15 especially if the individuals lived in states that did not legally recognize same-sex relationships 16 while other studies show reduced rates due to fear of discrimination. 17 This allows patients’ wishes to be respected and minimizes the chances of their loved ones experiencing disenfranchised grief, which is when an individual feels isolated in their grieving because their grief is not typically recognized by society at large.…”
Section: Barriers To Palliative Care Faced By Lgbtqia Patientsmentioning
confidence: 99%